Conocimiento y actitud sobre alimentación y su relación con el estado nutricional en las gestantes del Hospital Apoyo Iquitos, 2019 - Grandez Rios, Nataly Yulessy (Universidad Nacional de la Amazonía Peruana, 2021)
Feeding during pregnancy is particularly important since insufficient knowledge added with a negative attitude in the diet will affect the proper growth and development of the baby so that maintaining an adequate diet in quantity and quality of the mother will be able to meet the demands of her own and those of the baby, the purpose of this research was to relate the level of knowledge and attitude about the nutritional status of the pregnant women who come to the pre-natal office of the service of Ginecobstetricia of the Iquitos Support Hospital "Cesar Garayar García". The variable knowledge was measured with validated surveys, with a scale of attitude on food and nutritional status a nutritional assessment sheet of the pregnant party was made. The results were observed 35.2% have a normal pregestational BMI and 45.7% had inadequate weight gain for the current gestation weeks. In addition, 58.1% of pregnant women have a low level of knowledge in food, 65.7% a negative attitude towards food. With regard to the relationship between the variables knowledge and attitudes with nutritional status in the pregnant women interviewed, it is shown that there is a statistical relationship (p < 0.05 – p value s 0.008), (p < 0.05 – p value s 0.016) respectively. In conclusion, the study showed that there is a link between the level of knowledge and attitudes about food with nutritional status in pregnant women.

Durante el periodo de la gestación la nutrición adquiere gran importancia, ya que un conocimiento insuficiente sumado por actitudes negativas alimentarias afectará el crecimiento del feto, por lo que el mantenimiento de la calidad y cantidad adecuada de la madre podrá satisfacer las necesidades del bebe y las de ella. El propósito de esta investigación es relacionar el nivel de conocimiento y actitud sobre el estado nutricional de las gestantes que acuden al consultorio pre natal del servicio de Ginecobstetricia del Hospital Apoyo Iquitos “Cesar Garayar García”. Se midió la variable conocimiento con encuestas validadas, con una escala de actitud tipo Lickert y el estado nutricional se confeccionó una ficha de evaluación nutricional de la gestante. Los resultaron se observó el 35,2% tiene un IMC pregestacional normal y el 45,7% ganancia inadecuada de peso para las semanas de gestación actual. Asimismo, el 58,1% presento un nivel de conocimiento bajo en la alimentación, el 65,7% una actitud negativa hacia la alimentación. Respecto a la relación entre las variables conocimientos y actitudes con el estado nutricional en las gestantes entrevistadas, se muestra que existe relación estadística (p < 0,05 – p valor = 0,008), (p < 0,05 – p valor = 0,016) respectivamente. En conclusión, el estudio mostro que existe relación entre el nivel de conocimientos y actitudes sobre alimentación con el estado nutricional en las gestantes.
Keywords: Alimentación humana; Embarazo; Estado nutricional; Conocimientos, actitudes y prácticas; https://purl.org/pe-repo/ocde/ford#3.03.04